2006
DOI: 10.1161/01.hyp.0000222004.74872.17
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Genetic Hypertension by Suppression of Renal G Protein–Coupled Receptor Kinase Type 4 Expression

Abstract: Abstract-Abnormalities in D 1 dopamine receptor function in the kidney are present in some types of human essential and rodent genetic hypertension. We hypothesize that increased activity of G protein-coupled receptor kinase type 4 (GRK4) causes the impaired renal D 1 receptor function in hypertension. We measured renal GRK4 and D 1 and serine-phosphorylated D 1 receptors and determined the effect of decreasing renal GRK4 protein by the chronic renal cortical interstitial infusion (4 weeks) of GRK4 antisense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 37 publications
5
99
0
Order By: Relevance
“…Of the four GRK4 splice variants described in humans (11), only GRK4-␣, the full-length version, and GRK4-␥, which lacks the sequence encoded by exon 15 resulting in a 46-residue deletion near the C terminus, are able to phosphorylate D 3 R upon agonist activation. GRK4-␥ results in a 3-fold increase in D 3 R phosphorylation, whereas GRK4-␣ leads to a 2-fold increase, indicating that both variants are important in D 3 R signaling in hPTCs where all four GRK4 splice variants are expressed (44). The extent of GRK4-mediated D 3 R phosphorylation is similar to that observed in agonistactivated D 1 R by GRK4-␣ in HEK-293 cells (47).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Of the four GRK4 splice variants described in humans (11), only GRK4-␣, the full-length version, and GRK4-␥, which lacks the sequence encoded by exon 15 resulting in a 46-residue deletion near the C terminus, are able to phosphorylate D 3 R upon agonist activation. GRK4-␥ results in a 3-fold increase in D 3 R phosphorylation, whereas GRK4-␣ leads to a 2-fold increase, indicating that both variants are important in D 3 R signaling in hPTCs where all four GRK4 splice variants are expressed (44). The extent of GRK4-mediated D 3 R phosphorylation is similar to that observed in agonistactivated D 1 R by GRK4-␣ in HEK-293 cells (47).…”
Section: Discussionsupporting
confidence: 57%
“…in proximal and distal tubules and the glomeruli, and hence co-localization is mostly observed in these structures. Although GRK4 expression was first thought to be confined mainly to the testis and the brain (11,43), later reports showed that GRK4 isoforms, especially GRK4␥, are expressed in the human kidney (12,44), especially in the proximal tubules (13), and in other tissues, such as the human myometrium (45).…”
Section: Discussionmentioning
confidence: 99%
“…33 Renal GRK4 plays a role in the high blood pressure of SHRs. 21 Both GRK4 and GRK2 have been implicated in the D 1 R dysfunction in obese rats. 34 GRK2 activity is increased in SHRs and is responsible for the impaired renal D 1 R function with aging and hyperglycemia.…”
Section: Physiological Role Of Grk4mentioning
confidence: 99%
“…A fifth Grk4 isoform, Grk4E, which lacks exons 6 and 14, may be the functional isoform expressed in rat kidney cortex. 21 The differential tissue distribution of Grk4A, Grk4B, and Grk4E suggests that individual GRK4 splice variants may serve distinct physiological functions. …”
mentioning
confidence: 99%
“…Our present study found that stimulation of D 1 -like receptor with fenoldopam increases renalase expression in WKY cells but not in SHR cells. We have reported that the renal D 1 -like receptor function is impaired in SHRs due to the hyperphosphorylation of the D 1 receptor (17,31), which has been ascribed to increased constitutive activity of G protein-coupled receptor kinase 4 (GRK4) (17, 31). Whether or not this strategy is helpful in increasing renalase expression and activity in kidney of SHRs needs to be confirmed in the future.…”
Section: Discussionmentioning
confidence: 99%